(untitled) (Research, Society and Development, 2021)
This study aims to verify the use of video conferencing as an educational strategy in times of pandemic COVID-19. This is an integrative and literature review carried out in the following databases: Lilacs, SCiELO, Ibecs, Bdenf, WoS and PubMed in the period from 2019 to January 2021. The search was carried out through the following descriptors: Education; Videoconference and COVID-19. In total, 14 international publications were included in which the following categories emerged: videoconference, the dichotomy of facilitating and impeding aspects; the use of video conferencing in the educational context, secret experiences in times of COVID-19. The analysis of the articles showed that the use of video conferencing during the pandemic has boosted remote education, even in the face of many challenges, this resource has been favorable for students and teachers to continue academic activities, including with regard to professional training through availability of courses and training. In view of the uncertainties regarding the future of the educational system, it is not possible to say that remote education will replace classroom teaching, however, as an educational strategy it has been a plausible answer to the current situation.